The differential roles of shame and guilt in the relationship between self-discrepancy and psychological maladjustment - Oh, Hyunjoo; Lee, Dong-gwi; Cho, Hunggu (Frontiers in Psychology, 2023)
The self-discrepancy theory proposes that having inconsistent self-representations can trigger feelings of shame and guilt, leading to experiences of depression and anxiety. The aim of this study was to determine the distinct characteristics of each shame and guilt in relation to the connection between actual/ideal self-discrepancy and depression, as well as actual/ought self-discrepancy and anxiety. A total of 403 participants completed an online questionnaire assessing their self-discrepancy, shame, guilt, depression, and anxiety. Correlational analysis and structural equation modeling (SEM) analysis were used to assess the goodness of fit of the proposed model and the structural relationships between the variables. The key findings were as follows: (1) There were positive correlations among actual/ideal self-discrepancy, actual/ought self-discrepancy, shame, guilt, depression, and anxiety; (2) Shame partially mediated the association between actual/ideal self-discrepancy and depression; and (3) Guilt fully mediated the association between actual/ought self-discrepancy and anxiety. These outcomes uphold the self-discrepancy theory by confirming a distinct intra-psychological process involving shame and guilt. Each type of self-discrepancy was related to experiences of depression and anxiety. Our data suggest that researchers and practitioners should prioritize shame and guilt when examining individuals’ self-discrepancy and related mental health challenges.